The effect of an employer health insurance mandate on health insurance coverage and the demand for labor: evidence from Hawaii - Thomas C. Buchmueller; John DiNardo; Robert G. Valletta (Institute for the Study of Labor (IZA), 2009)
Over the past few decades, policy makers have considered employer mandates as a strategy for stemming the tide of declining health insurance coverage. In this paper we examine the long term effects of the only employer health insurance mandate that has ever been enforced in the United States, Hawaii's Prepaid Health Care Act, using a standard supply-demand framework and Current Population Survey data covering the years 1979 to 2005. During this period, the coverage gap between Hawaii and other states increased, as did real health insurance costs, implying a rising burden of the mandate on Hawaii's employers. We use a variant of the traditional permutation (placebo) test across all states to examine the magnitude and statistical properties of these growing coverage differences and their impacts on labor market outcomes, conditional on an extensive set of covariates. As expected, the coverage gap is larger for workers who tend to have low rates of coverage in the voluntary market (primarily those with lower skills). We also find that relative wages fell in Hawaii over time, but the estimates are statistically insignificant. By contrast, a parallel analysis of workers employed fewer than 20 hours per week indicates that the law significantly increased employers' reliance on such workers in order to reduce the burden of the mandate. We find no evidence suggesting that the law reduced employment probabilities.
urn:nbn:de:101:1-20090513509
Keywords: J32; I18; J23; 330; Health insurance; employment; hours; wages; Krankenversicherung; Betriebliche Sozialleistungen; Versicherungspflicht; Versicherungsschutz; Arbeitsnachfrage; Beschäftigungseffekt; Hawaii